What philosophy is for - Hampe, Michael, 1961- (The University of Chicago Press, 2018)
What is the state of philosophy today, and what might it be tomorrow? With What Philosophy Is For, Michael Hampe answers these questions by exploring the relationships among philosophy, education, science, and narrative, developing a Socratic critique of philosophical doctrines. Philosophers generally develop systematic theories that lay out the basic structures of human experience, in order to teach the rest of humanity how to rightly understand our place in the world. This "scientific" approach to philosophy, Hampe argues, is too one-sided. In this magnum opus of an essay, Hampe aims to rescue philosophy from its current narrow claims of doctrine and to remind us what it is really for--to productively disillusion us into clearer thinking. Hampe takes us through twenty-five hundred years of intellectual history, starting with Socrates. That archetype of the philosophical teacher did not develop strict doctrines and rules, but rather criticized and refuted doctrines. With the Socratic method, we see the power of narration at work. Narrative and analytical disillusionment, Hampe argues, are the most helpful long-term enterprises of thought, the ones most worth preserving and developing again. What Philosophy Is For is simultaneously an introduction, a critique, and a call to action. Hampe shows how and why philosophy became what it is today, and, crucially, shows what it could be once more, if it would only turn its back on its pretensions to dogma: a privileged space for reflecting on the human condition. --